The Relationship Between Mathematical Reasoning Ability and Self-Efficacy on Junior High School Students - Sari, Laras Mawar; Sumarmo, Utari; Supriatna, Tatang (IKIP Siliwangi, 2025)
This research is motivated by the significance of mathematical reasoning in problem solving, while self efficacy is considered to influence its development. The objective of this study is to the level of mathematical reasoning ability and self efficacy while also investigating the relationship between these two variables in SPLDV material. The study employs a quantitative approach with a correlational design. The research participants numbered 32 people from class VIII at a junior high school in Karawang Regency. Data collection was done using a mathematical reasoning ability test and a self efficacy questionnaire, both of which were analyzed through descriptive and inferential statistics. The descriptive analysis provides an overview of students mathematical reasoning ability and self efficacy levels, while the inferential analysis applies the Pearson Product Moment correlation test to determine the relationship between the two variables. The descriptive analysis revealed that the average score for students mathematical reasoning ability was 40.63, lacing it in the moderate category, indicating that not all indicators of mathematical reasoning were well achieved. The average self efficacy score was 86.34, which also falls within the moderate range. The inferential analysis showed a strong and significant relationship between mathematical reasoning ability and self efficacy, with a correlation coefficient value of 0,803 and Sig.(2-tailed) = 0,000 where 0,000 < 0.05. This reveals the greater the students self efficacy, the better their ability in mathematical reasoning.